Online Community and Citizen Science supports environmental science learning by young people - Herodotou, Christothea (Comput Educ, 2022)
Community and citizen science in online settings could be seen as a means for young people to engage with and contribute to authentic science. Yet, there is a limited understanding of who takes part in citizen science among young people, what they learn, and through which processes, particularly in online settings. In this exploratory study, we analysed 34 in-depth interviews and log files of young people aged 11–19 years old who took part in citizen science projects, hosted on the Zooniverse platform. Data analysis suggested that participation in online citizen science can bring environmental science learning benefits to young people, with some participants reporting evidence of agency with science, highlighted by taking action to do science in another context. Many participating youth exhibited substantial previous science experiences that helped them to take part and learn from citizen science projects. Considering findings from this study, we present a first working framework of how environmental science learning is enabled or hindered by certain types of participation, as a means to guide the design of online citizen science for young people. We recommend that the future project design, publicity and recruitment in online citizen science activities explicitly target the needs and interests of young people with diverse characteristics and competencies to truly open science to all.